2010
DOI: 10.1130/g31250.1
|View full text |Cite
|
Sign up to set email alerts
|

The Paleogene California River: Evidence of Mojave-Uinta paleodrainage from U-Pb ages of detrital zircons

Abstract: U-Pb age spectra of detrital zircons in samples from the Paleogene Colton Formation in the Uinta Basin of northeastern Utah and the Late Cretaceous McCoy Mountains Formation of southwestern Arizona (United States) are statistically indistinguishable. This fi nding refutes previous inferences that arkosic detritus of the Colton was derived from cratonic basement exposed by Laramide tectonism, and instead establishes the Cordilleran magmatic arc (which also provided sediment to the McCoy Mountains Formation) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 22 publications
2
56
1
Order By: Relevance
“…Howard (1996Howard ( , 2000 interpreted a large paleodrainage system to the southwest, to the Pacifi c Ocean, that would have been across the divide from these northeast-draining systems. In contrast, Davis et al (2010) proposed that a Late Paleocene-Early Eocene system drained northeastward from southeastern California to Utah, perpendicular to the drainage of Howard (1996Howard ( , 2000 ? ?…”
Section: Did Paleovalleys Cross the Southern Sierra Nevada?mentioning
confidence: 91%
See 1 more Smart Citation
“…Howard (1996Howard ( , 2000 interpreted a large paleodrainage system to the southwest, to the Pacifi c Ocean, that would have been across the divide from these northeast-draining systems. In contrast, Davis et al (2010) proposed that a Late Paleocene-Early Eocene system drained northeastward from southeastern California to Utah, perpendicular to the drainage of Howard (1996Howard ( , 2000 ? ?…”
Section: Did Paleovalleys Cross the Southern Sierra Nevada?mentioning
confidence: 91%
“…10 and 11). Davis et al (2010) interpreted that a Late Paleocene-Early Eocene drainage system (California River) extended northeast from southeastern California to northeastern Utah. In contrast, Howard (1996Howard ( , 2000 interpreted a Late Paleocene-Middle Miocene, ancestral Colorado River that drained southward across southeastern California, perpendicular to and across the drainage of Davis et al (2010), and then west to the Pacifi c Ocean (Fig.…”
Section: Regional Orogenic Highlandmentioning
confidence: 97%
“…Timing of the plateau uplift is poor, but there appears at least two phases of uplift, the most recent one is the last 5 Ma [11]. Driving mechanisms of plateau uplift have received considerable attention over the past four decades, since the broad acceptance of plate tectonics are still under debate [3]. When the geologic and geophysical data for the Plateau are considered, however, it seems likely that more than one mechanism is required to explain the 2 km of uplift [11].…”
Section: Modeling Of the Upliftmentioning
confidence: 98%
“…However, plateaus can also develop in intraplate regions, such as the Colorado Plateau in the western America, the Ordos Block in China or the southern African Plateau [4]. North plateaus underwent a series of uplift processes, the most recent estimate of elevation increase is more than 2 km, which we believe to be relative to thermal expansion associated with lithospheric thinning and magmatic-related crustal thickening [3]. Karlstrom et al [5] suggested a static framework for incision of the Grand Canyon which envisions a previously elevated Colorado Plateau that was passively incised by a deepening canyon system (and progressive watertable lowering) in response to base-level fall.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation